2021
DOI: 10.1590/0034-7329202100101
|View full text |Cite
|
Sign up to set email alerts
|

The institutionalized Buen Vivir: a new hegemonic political paradigm for Ecuador

Abstract: • Este é um artigo publicado em acesso aberto e distribuído sob os termos da Licença de Atribuição Creative Commons, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que o autor e a fonte originais sejam creditados.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In order to do this respectfully and transparently, we traced what Katz (2001Katz ( , p. 1229) calls the 'contour lines that represent not elevation but particular relations to a process'. In so doing, we demonstrated that buen vivir reframes and concretises the way in which social ruralities in this very different context offer up new narratives for a 'good coexistence' (Albo, 2017;Benalcázar & de la Rosa, 2021). However, our contribution to the literature on buen vivir goes beyond the geographical.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In order to do this respectfully and transparently, we traced what Katz (2001Katz ( , p. 1229) calls the 'contour lines that represent not elevation but particular relations to a process'. In so doing, we demonstrated that buen vivir reframes and concretises the way in which social ruralities in this very different context offer up new narratives for a 'good coexistence' (Albo, 2017;Benalcázar & de la Rosa, 2021). However, our contribution to the literature on buen vivir goes beyond the geographical.…”
Section: Discussionmentioning
confidence: 57%
“…However, our contribution to the literature on buen vivir goes beyond the geographical. Rather, in recognising their transformational and powerful role as social and political actors, we introduce (domestic) animals as a key constituency in efforts to achieve a more ‘harmonious relation between society and nature’ (Benalcázar & de la Rosa, 2021, p. 9).…”
Section: Discussionmentioning
confidence: 99%